Prevención de violencia de género en estudiantes de la Unidad Educativa “Vicente Anda Aguirre”. Riobamba. - Cuzco Quijosaca, Vanessa Cristina (2025)
The objective of the research was determinated the types of gender based violence in high school students from the “Vicente Anda Aguirre” Educational Unit. Riobamba. Gender based violence is any act that involves causing harm to another person based on their gender, whether psychologically, physically, sexually, economically, or otherwise. The methodology used was quantitative approach and non- experimental design. The type of research was descriptive in scope; basic in objectives; field type; cross sectional in time; the selected population was students from the Vicente Anda Aguirre Educational Unit and the sample consisted of first year students from high school, grades A, B and C, for a total of 110 students.The technique used was a survey and the instrument applied was a questionnaire; analysis of the results showed that students at the Vicente Anda Aguirre Educational Unit experienced all four types of violence, with psychological violence predominating in that order at 37%, economic violence at 26%, physical violence at 24% and sexual violence at 8%.